Relationship between Innovativeness and Strategic Planning - empirical research - Mamula, Tatjana; Popovic-Pantic, Sanja (Industrija, 2015)
This paper discusses a research of the relationship between innovativeness and strategic planning in SMEs. In introduction part, the authors attempt to consider relevant findings about this specific relationship in the literature. The paper presents how the EU policy approaches the innovation management system within SMEs and where Serbia stands in catching up the process towards the EU in terms of innovativeness and competitiveness.The main research approach is to examine the relationship between innovativeness and strategic orientation, beginning with the existence of the four key strategic business documents: strategic, marketing plan, business plan and procedures, and innovation strategy documents. The last part is a discussion on the findings and considerations of the intensity of the relations among strategic orientations of the company expressed through presence of the key strategic documents and innovativeness and relations among the three most practiced types of innovation in representative sample of 150 Serbian small and medium enterprises (SMEs).The research has shown that there is positive correlation between strategic planning approach in marketing and firm’s innovativness but the intensity of the relationship depends on the type of the innovativness considered.